Perencanaan Desain Offshore Kontruksi Bawah Laut menggunakan Pengolahan Data Pemodelan Geofisika dengan Program Simulasi 3D Surfer - Edy Soesanto; Aly Rasyid; Hadi Suyanto (Jurnal Bhara Petro Energi, 2022)
Underwater  construction  design  planning  is  increasingly  being  developed  as  a  3D  modeling simulation, because 3D simulation is expected to be able to make the initial plan for making a design  framework.  Surfer  is  one  of  the  software  that  was  created  for  the  purpose  of  making contour  maps  and  three-dimensional  modeling  based  on  existing  grids  and  simplifying  and accelerating data conversion activities into the form of contour maps and surface plots. One of the  applications  is  Surfer  in  the  field  of  Underwater  Technology  development  is  3D  modeling simulation and bathymetric contour map making, sediment layer modeling using SBP data and making current stick plots to determine circulation and current velocity and direction. In addition, Surfer can also display maps in 2D or 3D. on this occasion Surfer 16 software will be used to process  marine  acoustic  data  with  X  (Easting)  data,  Y  (Northing)  data  and  six  Z  layer  depths, namely Z1-Z6, the data is processed in one step to make 2D and 3D models which are then will be  interpreted  as  a  simulation  material  for  the  initial  planning  of  the  underwater  construction design.